Predicting determinants of hotel success and development using Structural Equation Modelling (SEM)-ANFIS method - Yadegaridehkordi, Elaheh; Nilashi, Mehrbakhsh; Md Nasir, Mohd Hairul Nizam; Ibrahim, Othman (Elsevier, 2018)
This study aimed to identify the relative importance of the Critical Success Factors (CSFs) that contribute to the success and development of hotel industry in Malaysia. Drawing uponTechnology-Organization-Environment (TOE) and Human-Organization-Technology (HOT) fit models, this study developed a theoretical model to predict the significant factors that contribute to the success and development of hotel industry. A two-stage Structural Equation Modelling (SEM)-Adaptive Neuro-Fuzzy Inference Systems (ANFIS) method was applied to test the research model and reveal the importance level of factors in the model. SEM analysis showed that the use of IT, financial performance, benchmarking, service standardization, top management support, customer satisfaction, service quality, hotel interior and exterior design/look, location, employee training and empowerment were significant factors influencing hotel success and development. Moreover, the results of ANFIS showed that customer satisfaction under human dimension was the most critical predictor of hotel success and development.